Corrigendum: Softec HD hydrophilic acrylic intraocular lens: biocompatibility and precision - Espandar L (Dove Medical Press, 2011)
Espandar L, Sikder S, Moshirfar M. Softec HD hydrophilic acrylic intraocular lens: biocompatibility and precision. Clin Ophthalmol. 2011;5:65–70.There was an error in the reported optic size of Lenstec’s Softec HD intraocular lens, which was reported to be 5.5 mm in Espandar et al’s work, but is 5.75 mm.Please see the specifications on Lenstec’s Web site for further details (see http://www.lenstec.com/lenstec/hd_specs.html).Read the original article